The Issue of Moving the Indonesian Capital: An Eco-Critical Discourse Analysis in Jokowi's Speech - Qulub, Muhammad Farihul (Centre for Literary and Cultural Studies, 2025)
This article aims to describe the representation of the issue of moving the Indonesian Capital City (IKN) through President Jokowi's speech, using an eco-critical discourse analysis approach based on Fairclough's three-dimensional model related to knowledge, beliefs, arts, morals, laws, customs, and other abilities acquired by a person as a society, threatening conditions and damage to the natural life of plants, animals, and humans. Data were collected from transcripts of Jokowi's speeches from 2019 to 2023, which circulated on social media and YouTube and had the most views and ratings. The analysis results show that Jokowi's speech represents the IKN as a project of renewal, equitable development, transformation of work culture, and ecology-based innovation. As well as how the use of language in the president's speech shapes public perceptions regarding ecological and social issues in the IKN relocation. The representation of this issue reflects Fairclough's dimensions (social practices, textual practices, discursive practices), so it is relevant to the global focus because it has a greater and more profound influence on many parties than social factors, language and cultural factors in Indonesia.